PERAN PEMERINTAH REPUBLIK INDONESIA DALAM MENANGGAPI TUDUHAN ATAS PELANGGARAN HAM DI PAPUA - Rahmah Sulaiman; Abdul Rahman; Sutiarnoto Sutiarnoto (Journal of USU International Law, 2017)
ABSTRACT THE ROLE OF THE GOVERNMENT OF THE REPUBLIC OF INDONESIA IN RESPONDING TO ALLEGATIONS OF HUMAN RIGHTS VIOLATIONS IN PAPUA Rahmah Sulaiman Abdul Rahman, S.H. M.H. Dr. Sutiarnoto, SH., M.Hum. The unitary state of the Republic of Indonesia is a sovereign State so that no country can intervene or interfere with any problems encountered by the Republic of Indonesia in its national scope.As recently seven countries in the Pacific Islands have alleged that Indonesia is violating human rights in Papua. It was expressed by them in the United Nations forum, and according to Indonesia it includes the attitude that intervenes the sovereignty of the Unitary State of Republic of Indonesia.Indonesia responds to it through its right of reply in the United Nations forum. The type of research used in writing this thesis is normative legal research. Also, in this study the method of legislation approach is used by using primary and secondary legal materials.The required data is collected by means of library research and then presented systematically and analyzed by qualitative analysis method. The results of this study indicate that Indonesia has played its part by responding to statements from seven Pacific Countries accusing Indonesia of violating human rights in Papua. Indonesia takes diplomatic action in its right of reply at the UN forum.In essence, Indonesia denies the allegation by stating that Indonesia is a country that upholds human rights in which, in this case, Indonesia has ratified eight out of nine human rights instruments.And Indonesia has also made legal efforts in enforcing human rights in Indonesia by establishing an official institution or commission dealing with human rights issues in Indonesia.Furthermore, Indonesia states that Indonesia has a mechanism to deal with problems in Papua without any unnecessary intervention from any party. Keywords: human rights, diplomatic action